2012
DOI: 10.4314/bcse.v27i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the concentration of Cr, Mn and Fe in sediment using laser-induced breakdown spectroscopy

Abstract: ABSTRACT. In the present study, laser-induced breakdown spectroscopy (LIBS) has been applied for the determination of levels of Cr, Mn and Fe in sediment samples and the results have been compared with that of flame-atomic absorption spectroscopy (F-AAS). Fourteen sediment samples were collected from Tinishu Akaki River (TAR), Addis Ababa, Ethiopia. Pellets of 24 mm in diameter and 3−5 mm in thickness were prepared using a manual hydraulic press under a pressure of 8000 psi by mixing finely ground sediment sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(30 reference statements)
0
4
1
Order By: Relevance
“…The LoD of Cr in rice powder using Cr line at 422.6 nm was 25 mg/kg; The Cr I 425.4 nm line was used as a representative for quantitative measurement because this line has the highest sensitivity compared to other Cr lines at 427.4 and 428.9 nm. This LoD is much lower compared to the result as described in the report [19], namely the LoD of Cr in powder material is 43 mg/kg. In the report, a standard LIBS using pulse Nd;YAG laser was employed and the powder material was prepared in the pellet form.…”
Section: ( )contrasting
confidence: 66%
“…The LoD of Cr in rice powder using Cr line at 422.6 nm was 25 mg/kg; The Cr I 425.4 nm line was used as a representative for quantitative measurement because this line has the highest sensitivity compared to other Cr lines at 427.4 and 428.9 nm. This LoD is much lower compared to the result as described in the report [19], namely the LoD of Cr in powder material is 43 mg/kg. In the report, a standard LIBS using pulse Nd;YAG laser was employed and the powder material was prepared in the pellet form.…”
Section: ( )contrasting
confidence: 66%
“…These high Mn contents, especially observed at LA1 where anthropogenic input is non-existent, can mainly be from weathering of the hydrothermally affected volcanic rocks near Addis Ababa (Alemayehu 2006). Compared with this, anthropogenic inputs from industrial activities such as the distilleries and battery factory in the area (Melaku et al 2005;Mekkonen et al 2013;Li et al 2014), are much less important. The above weathering process might also have caused an increase in the levels of other trace metals in the area (Alemayehu 2006;Alemayehu Abiye et al 2011).…”
Section: Resultsmentioning
confidence: 90%
“…For instance, Lazic et al [30] analyzed heavy metals traces in an Antarctic sediment core. Similarly, Barbini et al [31] reported the qualitative and quantitative analysis of several heavy metals in marine sediments extracted during the XI Italian Antarctic campaign. In another study, Cuñat et al [32] used a portable LIBS system to measure in situ traces of Pb in road sediments.…”
Section: Introductionmentioning
confidence: 93%